Effect of reduced glutathione on the liquid storage (5Â°C) of mithun semen - PERUMAL, P; VUPRU, KEZHAVITUO; RAJKHOWA, C (The Indian Journal of Animal Sciences, 2013)
The present study was undertaken to assess effect of reduced glutathione (GSH) on sperm motility, viability, total sperm abnormality, acrosomal and plasma membrane integrity, super oxide dismutase(SOD)and catalase, cholesterol efflux and malonaldehyde (MDA) production. Ejaculates (50) were collected twice a week from 8 mithun bulls and semen was split into 4 equal aliquots, diluted with the TEYC extender. Group 1: semen without additives (control), group 2 to group 4:semen was diluted with 5 mM, 10 mM and 15 mM of reduced glutathione (GSH), respectively. Inclusion of GSH into diluent resulted in significant decrease in percentages of dead spermatozoa, abnormal spermatozoa and acrosomal integrity at different hours of storage periods as compared with control group. Additionally, GSH at 5 and 15 mM were inferior to GSH 10 mM treatments as regards to these characteristics and GSH at 10 mM has significant improvement in quality of mithun semen in in- vitro stored for up to 30 h. It was concluded that the possible protective effects of GSH on sperm parameters are, it enhanced the function of antioxidant enzymes, prevented efflux of cholesterol from cell membrane, and reduced malonaldehyde(MDA) production during preservation.